Proximal fibular stress fracture in adolecent soccer player. A case report - Pogliacomi, Francesco; Longhi, Alberto; Ferrari, Umberto; Schiavi, Paolo; Pedrazzini, Alessio; Vaienti, Enrico; Ceccarelli, Francesco; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2023)
Fibular fractures are the third most common stress fractures in children and adolescents. Proximal fibular location is a very rare finding, with few reports in the literature and, frequently, careful investigations before a definitive diagnosis could be necessary. The authors report a case of an adolescent 13 years old soccer player with a proximal fibular fracture that was initially underestimated and misdiagnosed and ultimately confirmed as a stress lesion by MRI.